Colorectal Carcinoma in A 12 Year Old Child: A Case Report - Bhatia, Gunjan; Goyal, Namita; Bhargava, Sunita (Annals of Pathology and Laboratory Medicine, 2019)
Colorectal carcinoma is a rarely seen malignancy among children. The prognosis of colorectal carcinoma is poorer among children as compared to adults due t o lack of awareness among treating pediatricians and surgeons regarding this entity. A 12 year old female child presented with complaints of recurrent abdominal pain, fullness of abdomen, poor appetite since last 2 years. Abdominal ultrasound was suggestive of a mass arising from the right hypochondrium. Colonoscopy and biopsy confirmed the diagnosis of adenocarcinoma. The possibility of colorectal carcinoma as a differential diagnosis should always be considered in a child who presents with signs and symptoms of intestinal obstruction, intractable abdominal pain, altered bowel habits, long standing abdominal distension and gastrointestinal bleeding. Colorectal carcinoma should not be excluded as a possibility only based on patient’s age.